Quasiribbon vacuum arc ion source "Raduga-6"; 9th International Conference on Modification of Materials with Particle Beams and Plasma Flows, Tomsk, 21-21September 2008 - Ryabchikov A. I. Aleksandr Ilyich; Stepanov I. B. Igor Borisovich; Eremin S. E.; Sivin D. O. Denis Olegovich
The results on research and developmentof new modification of a high-current quasiribbonrepetitively-pulsed ion and plasma source "Raduga-6" on the basis of extended vacuum-arcevaporator generating plasma by a dc vacuum-arcare presented in the article. A new modification ofa time-of-flight extended plasma filter was developedand used for metal plasma filtering from microparticlefraction. Research and developmentof a model of extended vacuum-arc evaporator andplasma filter adapted for it have been described